Volume 6: 33rd Design Automation Conference, Parts a and B 2007
DOI: 10.1115/detc2007-35382
|View full text |Cite
|
Sign up to set email alerts
|

Representing Historically Based Component-Function Relationships Through Design Templates

Abstract: Functional analysis of systems is a common engineering application during different stages of design. Conceptual designers as well as post-development designers use the process to gather useful information about the system that is under consideration. The functional basis and component taxonomy are collective approaches to describe these systems in unique languages. Since many designers naturally think in terms of physical components, it is more difficult for them to grasp fundamental concepts necessary to fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Hannah defined design templates as reusable design process modules that support decision-making at various stages in the design process (1) . Abbott focused on the importance of functional templates and showed that a template tool for functional modeling helps a user develop modeling skills even if he/she does not possess extensive background knowledge (2) (3) . Nonetheless, there are three difficulties involved in template-based design.…”
Section: Product Design Based On Knowledge Templatementioning
confidence: 99%
“…Hannah defined design templates as reusable design process modules that support decision-making at various stages in the design process (1) . Abbott focused on the importance of functional templates and showed that a template tool for functional modeling helps a user develop modeling skills even if he/she does not possess extensive background knowledge (2) (3) . Nonetheless, there are three difficulties involved in template-based design.…”
Section: Product Design Based On Knowledge Templatementioning
confidence: 99%
“…A lecture discussing the component functional templates was given the following class period to the students. The lecture concluded with a bicycle transmission example presented in a Journal of Design Studies article 16 . A set of function chains was created Page 13.878.5…”
Section: Stagementioning
confidence: 99%
“…Previous research by the authors showed that historical relationships could be found between common electro-mechanical components and their associated functions 12 . A design tool, termed component functional templates, was developed to assist the functional modeling process.…”
Section: Introductionmentioning
confidence: 99%